Individual Differences in Conditioned Fear and Extinction in Female Rats - Tryon, Sarah C.; Sakamoto, Iris M.; Kellis, Devin M.; Kaigler, Kris F.; Wilson, Marlene A. (Frontiers in Behavioral Neuroscience, 2021)
The inability to extinguish a traumatic memory is a key aspect of post-traumatic stress disorder (PTSD). While PTSD affects 10-20 percent of individuals who experience a trauma, women are particularly susceptible to developing the disorder. Despite this notable female vulnerability, few studies have investigated this particular resistance to fear extinction observed in females. Similar to humans, rodent models of Pavlovian fear learning and extinction show a wide range of individual differences in fear learning and extinction, although female rodents are considerably understudied. Therefore, the present study examined individual differences in fear responses, including freezing behavior and ultrasonic vocalizations (USVs), of female Long Evans rats during acquisition of fear conditioning and cued fear extinction. Similar to prior studies in males, female rats displayed individual variation in freezing during cued fear extinction and were divided into extinction competent (EC) and extinction resistant (ER) phenotypes. Differences in freezing between ER and EC females were accompanied by shifts in rearing during extinction, but no darting was seen in any trial. Freezing behavior during fear learning did not differ between the EC and ER females. Vocalizations emitted in the 22 and 50 kHz ranges during fear learning and extinction were also examined. Unlike vocalizations seen in previous studies in males, very few 22 kHz distress vocalizations were emitted by female rats during fear acquisition and extinction, with no difference between ER and EC groups. Interestingly, all female rats produced significant levels of 50 kHz USVs, and EC females emitted significantly more 50 kHz USVs than ER rats. This difference in 50 kHz USVs was most apparent during initial exposure to the testing environment. These results suggest that like males, female rodents show individual differences in both freezing and USVs during fear extinction, although females appear to vocalize more in the 50 kHz range especially during initial periods of exposure to the testing environment and emit very few of the 22 kHz distress calls that are typically observed in males during fear learning or extinction paradigms. Overall, these findings show that female rodents display fear behavior repertoires divergent from males.